2022
DOI: 10.1097/hjh.0000000000003335
|View full text |Cite
|
Sign up to set email alerts
|

Concomitantly higher resting arterial blood pressure and transduction of sympathetic neural activity in human obesity without hypertension

Abstract: Objective: Central (abdominal) obesity is associated with elevated adrenergic activity and arterial blood pressure (BP). Therefore, we tested the hypothesis that transduction of spontaneous muscle sympathetic nerve activity (MSNA) to BP, that is, sympathetic transduction, is augmented in abdominal obesity (increased waist circumference) and positively related to prevailing BP.Methods: Young/middle-aged obese (32 AE 7 years; BMI: 36 AE 5 kg/m 2 , n ¼ 14) and nonobese (29 AE 10 years; BMI: 23 AE 4 kg/m 2 , n ¼ 1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 66 publications
0
2
0
Order By: Relevance
“…Having an elevated Body Mass Index (BMI) is the most commonly used way to gauge if one is at risk of forming kidney stones ( 7 , 8 ), which can be caused by being overweight. However, BMI is not without its drawbacks ( 9 ).…”
Section: Introductionmentioning
confidence: 99%
“…Having an elevated Body Mass Index (BMI) is the most commonly used way to gauge if one is at risk of forming kidney stones ( 7 , 8 ), which can be caused by being overweight. However, BMI is not without its drawbacks ( 9 ).…”
Section: Introductionmentioning
confidence: 99%
“…The analysis of the Health Professionals Follow-up Study and the Nurses’ Health Study I and II identified associations between obesity, diabetes, and kidney stone disease ( 8 , 9 ). Currently, the most commonly used measure of obesity is BMI (Body Mass Index) ( 10 ). However, BMI has some limitations, such as the inability to distinguish between lean body mass and fat body weight ( 11 ).…”
Section: Introductionmentioning
confidence: 99%